For the Nullity of the Will When It’s Sole or Decisive Reason Is in Contrary to the Law - Tsvetanov, Ivan; Nikolov, Nikolai; Dobrev, Valentin (Research Papers, 2024)
The purpose of this article is to give one of the possible answers to the interpretative question posed in interpretative case No. 2/2023 of the General Assembly of the Civil College (OSGK) of the Supreme Court of Cassation (SCC), namely "is it nullity on the grounds Art. 42, b. „c“ of the Inheritance Act (IA) a will which is made both for the care already taken of the testator and with a view to future care to be taken of him for the rest of his life; can in such a case, when interpreting the will of the testator, it be assumed that the only motive for making the will is contrary to the law, since it violates the principle of gratuity of the testamentary disposition?' In order to justify the answer proposed in this article, both the current judicial practice related to the posed question and the achievements of the Bulgarian civilist doctrine were used. Undoubtedly, the answer to this question will have a significant practical significance, as it will predetermine the direction of development of future judicial practice in this matter.
Keywords: Will; Nullity; One motive; Controversial with law